2017
DOI: 10.1007/s40750-017-0081-0
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Attractiveness and Health in Men’s Faces: the Impact of Color Cues and Variation in Relation to Sex and Age of Rater

Abstract: Cues available in facial skin are used to assess mate quality in humans and non-human primates. In men, perception of skin healthiness and facial attractiveness are associated with heterozygosity at genes in the major histocompatibility complex, with potential implications for securing direct benefits through mate choice. There is, however, some debate as to the precise nature of the information available in skin that is used in health and attractiveness judgments. Here we investigate whether color cues are im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Various studies have been carried out to explore the effect of facial color cue and luminance on people’s social perception [ 42 , 79 ]. Numerous researches have shown that evaluations of attractiveness could be influenced by the difference in skin color and condition [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have been carried out to explore the effect of facial color cue and luminance on people’s social perception [ 42 , 79 ]. Numerous researches have shown that evaluations of attractiveness could be influenced by the difference in skin color and condition [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the judgments of trustworthiness, researchers [ 42 ] have shown that cosmetics (vs. without cosmetics) could increase facial luminance and color cue, which, in return, improved the perception of likability, attractiveness, and trustworthiness. Similarly, researchers [ 79 ] suggest that color hue could have an impact on the evaluation of attractiveness in the face and healthiness in the skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pound et al, 2014 ). Finally, observers’ ratings of others’ health are sometimes associated with phenotypic mate-value traits (Roberts et al, 2017 ), such as homogeneous and carotenoid skin coloration (Fink et al, 2001 , 2006 ; Henderson et al, 2017 ; Jones, 2018 ), a more masculine voice (Albert et al, 2021 ), and facial averageness (Jones, 2018 ), whereas other studies have found weak or inconsistent links (e.g., Foo et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%